Chaya Leaf Decreased Triglycerides and Improved Oxidative Stress in Subjects With Dyslipidemia - Guevara-Cruz, Martha; Medina-Vera, Isabel; Cu-Cañetas, Trinidad Eugenia; Cordero-Chan, Yusef; Torres, Nimbe; Tovar, Armando R.; Márquez-Mota, Claudia; Talamantes-Gómez, José Moisés; Pérez-Monter, Carlos; Lugo, Roberto; Gutiérrez-Solis, Ana Ligia; Avila-Nava, Azalia (Frontiers in Nutrition, 2021)
Chaya is an edible leaf popular in Mexico and Central America because of its high nutritional value. Studies in animal models have demonstrated the beneficial effects of Chaya, which include reduction of circulating lipids and increase in antioxidant activity. However, its hypolipidemic and antioxidant effects have not been demonstrated in humans. Thus, the aim of the present study was to evaluate the effect of Chaya on the lipid profile, lipid peroxidation, inflammation, and peripheral blood mononuclear cell gene expression in a population with dyslipidemia. We performed a single-arm trial in 30 participants with dyslipidemia who consumed 500 mL of Chaya beverage per day over a 6-week period. Interestingly, we observed a significant decrease in serum triglyceride concentration (P < 0.05) and an increase in plasma antioxidant activity and polyphenol concentration (P < 0.005) after 6 weeks of Chaya consumption. This was accompanied by a reduction in the oxidative stress marker MDA (P < 0.0001) and by an increase in the antioxidant enzyme CAT expression in peripheral blood mononuclear cells (P < 0.001). Altogether, our results demonstrate that consumption of Chaya has hypotriglyceridemic and antioxidant effects in subjects with dyslipidemia.